COMPARISON OF THE DETERMINISTIC AND STOCHASTIC APPROACHES FOR ESTIMATING TECHNICAL EFFICIENCY ON THE EXAMPLE OF NON-PARAMETRIC DEA AND PARAMETRIC SFA METHODS - Bezat, Agnieszka (Metody Ilościowe w Badaniach Ekonomicznych, 2009)
The author considers in the article estimation of the technicalefficiency, which measures the ability of the company to obtain the maximum output from given inputs or to use the minimum input to achieve givenoutputs. The comparison of two approaches: deterministic (on the example ofData Envelopment Analysis) and stochastic (on the example of StochasticFrontier Approach) has been carried out, the advantages and disadvantages ofboth were also described. These methods were chosen because they have become popular in polish research. In the article the possible limitations andproblems, which may influence results of studies conducted by using thesemethods, were considered